Skill level of basic techniques service badminton on student Physical education - Ilmul Ma'arif; Risfandi Setyawan; Rahayu Prasetiyo (Universitas Sebelas Maret, 2024)
This study aims to determine the level of basic badminton serving skills in physical education students, this research method with a descriptive quantitative approach with survey methods, for the results of research on short serving skills, showed that of the 65 students who were in the excellent category 1, there were 21 students (32.31%), which included a medium category of 30 students (46. 15%), and the category is less 13 students (20%), in the category of less once there are 0 (0%), while for the long serve shows that no one is in the category of excellent 0 (0%), 23 students (35.39%) are in a good category, for the medium category 28 students (43.08%), 10 students (15.38%) are in the category of less, while 4 students (6.15%) are in the category of less once. As for the calculation of descriptive statistics on short service skills, the minimum value is 30, the maximum value is 37, for an average of 32.86, while for standard deviation it is 1.77, for the long service shows a score of at least 26, the maximum score is 36, for an average of 32.73, while for standard deviation shows 2.33. The conclusion based on the objectives and results of the research analysis states that the level of badminton serving skills of students is in the moderate category.